EXPLORING SERVICE QUALITY IMPACTS ON CUSTOMER SATISFACTION IN MILITARY MEDICAL CENTRES: MODERATING ROLE OF PERCEIVED VALUE - Ismail, Azman; Ali, Mohd Helmi; Rose, Nur Ilyani Ranlan; Abdulla, Anis Anisah; Rosnan, Herwina (Jurnal Dinamika Manajemen, 2016)
Much has been written about service quality impacts on customer satisfaction. However, little research on this perspective has been carried out in military settings. The aim of this study is to examine the relationship between service quality and customer satisfaction, and moderating effects of perceived value in military medical centre. A survey method was employed and data was collected from customers at medical centers under the administration of Malaysian army organization. Analysis was performed using SmartPLS path model analysis. The results show two important findings: first, the interaction between four service quality components (i.e., tangible, reliability, responsiveness and assurance) and customersâ perceived value were significantly correlated with customer satisfaction. Second, the interaction between one service quality component (i.e., tangible) were not significantly correlated with customer satisfaction. In overall, this result confirms that effect of tangible, reliability, responsiveness and assurance on customer satisfaction has been moderated by customersâ perceived value. Conversely, effect empathy on customer satisfaction has not been moderated by customersâ perceived value. Further, this study offers discussion, implications and conclusion.